Bystanders or not? Microglia and lymphocytes in aging and stroke - Nguyen, Justin; Chauhan, Anjali (Neural regeneration research, 2023)
As the average age of the world population increases, more people will face debilitating aging-associated conditions, including dementia and stroke. Not only does the incidence of these conditions increase with age, but the recovery afterward is often worse in older patients. Researchers and health professionals must unveil and understand the factors behind age-associated diseases to develop a therapy for older patients. Aging causes profound changes in the immune system including the activation of microglia in the brain. Activated microglia promote T lymphocyte transmigration leading to an increase in neuroinflammation, white matter damage, and cognitive impairment in both older humans and rodents. The presence of T and B lymphocytes is observed in the aged brain and correlates with worse stroke outcomes. Preclinical strategies in stroke target either microglia or the lymphocytes or the communications between them to promote functional recovery in aged subjects. In this review, we examine the role of the microglia and T and B lymphocytes in aging and how they contribute to cognitive impairment. Additionally, we provide an important update on the contribution of these cells and their interactions in preclinical aged stroke.